Identitas Politik Catalonia dalam Simbol-Simbol Football Club Barcelona - Nanda Rizka Syafriani Nasution; Fernanda Putra Adella (Politeia: Jurnal Ilmu Politik, 2018)
Football and politics are now two things that can not be separated. The development of football is increasingly rapidly making this sport a source and an instrument to obtain certain goals. The goal can be at variance, ranging from the acquisition of capital to power, existence, and ideologization. This research on two objects that missed will use secondary data as data collection technique that is in the form of book literature, local and international journal, as well as other materials that support and relate to the title of research including mass media and using study of qualitative analysis as technique in analyzing data. There are three representations of FC Barcelona symbols of Catalan political identity, namely: First, language and flags; Secondly, Catalan and FC Barcelona have dark memories of history; Third, the symbols that exist in FC Barcelona is a representation of the spirit of Catalan nationalism.